A utilização dos jogos digitais como mediadores na prática psicoterapêutica. - Felipe, Rhayssa Cavalcanti de Barros (2020)
This dissertation arose from our clinical experience and aimed to investigate the use of digital games as mediators in psychotherapeutic practice, from the report of psychologists working in the clinical area, for more than two years, and who already use digital games as mediators in their performance. The present study corresponds to a qualitative research of a psychoanalytic nature and is divided into two distinct stages: the first corresponds to the theoretical framework used in its construction, in which a bibliographic research was used, based on collected studies that bring relevant information the objectives outlined in this study. The second stage, on the other hand, deals with field research, carried out with six psychotherapists interviewed based on a semi-structured interview subdivided into eight categories. We were able to observe that the use of digital games as mediators in psychotherapy brings, in several aspects, benefits to the therapeutic process regarding the therapeutic practice and its reflexes in the patient. It is important to emphasize that the use of digital games is just another instrument within the wide range of possibilities of therapeutic mediators, a data also brought by the same psychologists interviewed. It was found that this is a mediator who travels in different therapy spaces, for the most varied audience, with age or socioeconomic condition not being an impeding factor in the benefits brought by digital games. It is a current resource that arouses interest, favors, among others, cognitive stimulation and enables a new clinical view of psychotherapy. The study also set out to stimulate further research on the topic, which will provide psychologists with a greater basis and security for the use of digital games in their practices.